Radioiodine therapy of Graves’ disease — a dosimetric comparison of different strategies concerning antithyroid drugs - Urbannek, V.; Voth, E.; Moka, D.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: Premedication with antithyroid drugs (ATD) compared to patients not pretreated with ATD causes a higher failure rate of radioiodine therapy (RITh) or demands higher therapeutical dosage of radioiodine (Rl). For clinical reasons and because of accelerated iodine metabolism in hyperthyreosis a compensated thyroid metabolism is desirable. Aim of this study was to investigate the influence of ATD on the biokinetics of Rl in case of Graves’ disease in order to improve RITh of patients pretreated with ATD. Methods: 385 consecutive patients who underwent RITh because of Graves’ disease for the first time were included: Group A (n = 74): RITh under continuous medication with ATD; Group B (ç = 111): Application of Rl under continuous medication with ATD, in case of insufficient Rl-uptake or shortened effective Rl-half-life ATD were stopped 1-5 days after RITh; Group C (n = 200): ATD were stopped 2 days prior to RITh in all patients. We examined the influence of ATD on Rl-uptake and effective Rl-half-life as well as the absorbed dose achieved on the thyroid in dependence of thyroid volume and applied Rl-dosage [TEQ - therapy efficiency quotient, (2)]. Results: In the Rl-pretest (all patients under ATD) the Rl-uptake was comparable in all three groups. During RITh Rl-uptake, effective Rl-half-life and therefore the TEQ were significantly higher in Group C as compared to Groups A and B (ñ <0,001, respectively). In Group B the medication with ATD was stopped in 61 of 111 cases 1-5 days after RITh. In this subgroup the effective Rl-half-life increased from 4,4 ± 1,7 d to 5,1 ± 1,6 d after stopping of ATD (ñ = 0,001). Conclusion: Stopping of ATD 2 days prior to RITh leads to an increased efficiency of about 50% compared to RITh carried out under ATD and therefore to a clear reduction of radiation exposure to the rest of the body with equal absorbed doses of the thyroid. Stopping of ATD shortly after RITh increases efficiency in case of short effective Rl-half-life, but it is inferior to stopping ATD 2 days prior to RITh.
Keywords: Antihyroid drugs; radioiodine therapy; half-life of 1-131; uptake of 1-131; Graves’ disease